A Review of Conservative Treatment of Acute Appendicitis - Svensson, J. F.; Hall, N. J.; Eaton, S.; Pierro, A.; Wester, T. (European Journal of Pediatric Surgery, 2012)
Appendicitis is a common condition in the pediatric population and appendectomy has been the traditional treatment. Both the urgency of the operation and the need for the appendectomy have recently been challenged. In children, this controversy focuses on operative management of perforated appendicitis and appendix abscesses. In adults, the debate has extended to management of nonperforated appendicitis. This review describes the evidence behind these challenges and updates a per-protocol meta-analysis of randomized controlled trials in adults. In the per-protocol meta-analysis, there was no difference between operative versus nonoperative management in failure of treatment. The complication rate was significantly lower in patients treated nonoperatively. However, in the nonoperative group, 10% of patients needed immediate surgery and 17% developed a recurrence during the 1-year follow-up. Overall, 73% of adults with suspected acute appendicitis may not need operative treatment. There are no data in the literature to support nonoperative treatment of acute appendicitis in children.
Keywords: acute appendicitis; appendectomy; pediatric population; conservative treatment